PENGARUH BRAND AMBASSADOR, PERSONALIZATION, DAN FOMO TERHADAP IMPULSE BUYING GENERASI Z PADA PLATFORM E-COMMERCE DI KOTA SURABAYA - Intan Anggun Dwi Liany; Finisica Dwijayati Patrikha (Jurnal Pendidikan Tata Niaga (JPTN), 2026)
This study aims to analyze and explain the influence of Brand Ambassador, Personalization, and Fear of Missing Out (FOMO) on the Impulse Buying behavior of Generation Z on e-commerce platforms in Surabaya. The research method employed is quantitative with a causal associative approach. The population for this study consists of Generation Z individuals in Surabaya, with a sample size of 391 respondents determined through a non-probability sampling technique using a purposive sampling approach. Data were collected via questionnaires and analyzed using multiple linear regression. The results indicate that, simultaneously, Brand Ambassador, Personalization, and FOMO have a positive influence on the Impulse Buying behavior of Generation Z in Surabaya. Partially, Brand Ambassador has a positive effect through the attractiveness of public figures that build emotional engagement. Personalization has a positive effect through relevant recommendation algorithms that simplify the product search process. Similarly, FOMO has a positive effect as a result of social anxiety regarding missing out on viral lifestyle product trends. The integration of these three variables is proven to create a persuasive shopping experience and trigger unplanned purchasing actions. Keywords: Brand Ambassador; FOMO; Generation Z; Impulse Buying; Personalization.